The effect of an HIV-1 viral protease inhibitor on staurosporine-induced apoptosis in immortalized mesangial cells - Serone, Adrian Pierce; Camargo, Simone Mafalda Rodrigues; Schor, Nestor (São Paulo Medical Journal, 2002)
CONTEXT: Progressive glomerular sclerosis is a condition characterized by the accumulation of glomerular extracellular matrix and a decrease in the number of glomerular cells. The mechanisms involved in the progressive loss of glomerular cells are not well understood but may involve the process of apoptosis. The principal mediators for the apoptotic pathway are a class of protease enzymes called caspases. It is not known how other therapeutic protease inhibitors affect the caspase cascade and therefore whether they would be effective in preventing excessive apoptosis in the late stages of progressive glomerular sclerosis. OBJECTIVE: To evaluate whether an inhibitor of the HIV1 viral protease Ac-Leu-Val-phenylalanine (PI) could inhibit apoptosis in immortalized mesangial cells. DESIGN: Experimental. SETTING: Nephrology Division, Universidade Federal de São Paulo/Escola Paulista de Medicina. PARTICIPANTS: Immortalized mesangial cells. PROCEDURES: Cell culture. MAIN MEASUREMENTS: Viability and rate of apoptosis. RESULTS: Immortalized mesangial cells were treated with staurosporine (at concentrations of 10-100 nM for 8-28 hours) to induce apoptosis. Staurosporine at 10 nM for 8 hours had no effect on viability, but did cause a significant increase in the rate of apoptosis (p = 0.0411, n = 6). Increasing the incubation time elicited a greater increase in the rate of apoptosis (p = 0.0001, n = 6), although there was also a significant decrease in viability (p=0.0002). Increasing the concentration of staurosporine to 100 nM resulted in a marked increase in apoptosis (p <0.0001) but resulted in unacceptable viability (<40%, p <0.0001, n = 6). CONCLUSIONS: Incubation of immortalized mesangial cells with PI (900 nM) alone for 2-24 hours had no effect on cell viability or the rate of apoptosis when compared with vehicle (methanol) controls. Coincubation of the cells with staurosporine (10 nM) and PI for 24 hours had no significant effect on the rate of apoptosis. Therefore, in immortalized mesangial cells, staurosporine-induced apoptosis was not significantly affected by the HIV-1 viral protease inhibitor Ac-Leu-Val-phenylalanine.